Strategi dan Inovasi Model Bisnis Katering dalam Meningkatkan Daya Saing di Era Pasar Digital - Auderey G. Tangkudung; Pinkan L. Sompie; Uteng Mahdi (Jurnal Syntax Admiration, 2024)
Micro, Small and Medium Enterprises (MSMEs) often face severe challenges during the global economic crisis, especially during the Covid-19 pandemic. MSMEs are encouraged to have strategies and innovations in order to face the crisis. This study aims to analyze catering business model strategies and innovations in improving post-pandemic competitiveness. This research uses qualitative methods with data collection through observation, literature review and in-depth interviews. Observations were made on three MSMEs engaged in catering. In-depth interviews were conducted with five MSMEs who were willing to be asked for information directly. This data analysis uses data reduction, data presentation and conclusions. The results of this study highlight several streams of catering business strategies and innovations carried out by MSMEs after the post COVID-19 pandemic. In addition, MSMEs can also turn challenges into opportunities through product innovation. This research has implications for adequate preparation and understanding of strategies and business model innovations that can be done to reduce the negative impact of the global crisis. Thus, this study can help the government in supporting MSMEs to be able to overcome the global crisis.